Pronounced Effect of Antibacterial Bioactive Dental Composite on Microcosm Biofilms Derived From Patients With Root Carious Lesions - Balhaddad, Abdulrahman A.; Ibrahim, Maria S.; Garcia, Isadora M.; Collares, Fabrício M.; Weir, Michael D.; Xu, Hockin H.; Melo, Mary Anne S. (Frontiers in Materials, 2020)
Resin composites are the material of choice for dental restorative treatment in oral health care. However, the inherent composition of this class of material commonly results in microbial adherence and colonization, which carries the potential risk of recurrent carious lesions around dental restorations. The high risk of dental composites failure complicates the treatment of root caries, defined as the onset of tooth decay over the prone root surface of a tooth. The restorative treatment of root caries among high caries risk individuals, especially for senior patients, is a challenging, painful, and costly. This study assesses the antibiofilm performance of a surface contact killing antibacterial dental resin composites on the growth of microcosm biofilms using dental plaque sampled from patients with active root carious lesions as an inoculum. The designed formulations contain dimethylaminohexadecyl methacrylate (DMAHDM), a tailored quaternary ammonium monomer with an alkyl chain length of 16, at 3-5 wt.% in a base resin with and without 20 wt.% nanoparticles of amorphous calcium phosphate (NACP). Biofilms were grown on the tested resin composites using a 48 h plaque-derived microcosm biofilm model. Dental plaque collected from active root carious lesions was used as an inoculum to emulate the microbiota present in those lesions. The biofilm growth was assessed via the colony-forming unit (CFU) counts in four culture media, metabolic behavior, lactic acid production, and confocal microscopy. The percentage of reacted double bonds of the formulations was also investigated. The dental resin composites formulated with 3-5 wt.% DMAHDM and 20 wt.% NACP were effective at eradicating surface-attached biofilms from the total microbial load and each relevant cariogenic group: total streptococci, mutans streptococci, and lactobacilli. The metabolic activities and lactic acid production of the plaque-derived microcosm biofilms were reduced by 80-95%, respectively. Fewer viable microorganisms were observed over resin composites containing DMAHDM and NACP. Besides, all the experimental formulations demonstrated an acceptable degree of conversion values. This new strategy fits with ongoing dental caries preventive and minimally invasive approaches by preventing biofilm growth over-restored carious root lesions and improving the lifespan of dental restorations.